2014
DOI: 10.1186/1471-2458-14-913
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health check attendance in adults: findings from the cross-sectional German Health Update (GEDA) study

Abstract: BackgroundIn Germany, adult health checks are carried out in the primary care setting for early detection of chronic conditions, such as cardiovascular diseases, diabetes, and kidney disease. This study aims to examine the social, behavioural, and health-related determinants of health check attendance among eligible adults in Germany.MethodsData were derived from the cross-sectional German Health Update (GEDA) study, a national health survey among adults in Germany carried out by the Robert Koch Institute. Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 52 publications
8
87
2
2
Order By: Relevance
“…Furthermore, our findings confirm those of previous studies; that the relative risk of attending the health check was higher in persons of higher age, with higher educational attainment, and more use of preventive services. In contrast, factors associated with a reduction in the relative risk of attending were: living alone, receiving social welfare or being un-employed, and morbidity (Artac et al, 2013, Hoebel et al, 2014, Fossa et al, 2015, Tolonen et al, 2015, Hoebel et al, 2013). The findings on morbidity and treatment are novel and provide a detailed picture of the diagnosis and treatment status and how this is associated with attendance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, our findings confirm those of previous studies; that the relative risk of attending the health check was higher in persons of higher age, with higher educational attainment, and more use of preventive services. In contrast, factors associated with a reduction in the relative risk of attending were: living alone, receiving social welfare or being un-employed, and morbidity (Artac et al, 2013, Hoebel et al, 2014, Fossa et al, 2015, Tolonen et al, 2015, Hoebel et al, 2013). The findings on morbidity and treatment are novel and provide a detailed picture of the diagnosis and treatment status and how this is associated with attendance.…”
Section: Discussionmentioning
confidence: 93%
“…A well-known challenge of screening and systematic health checks is low uptake (Krogsbøll et al, 2012) which seems to be influenced by a number of factors (Dryden et al, 2012, Bender et al, 2012). A higher participation rate has, in many studies, been found to be associated with higher age (Jones et al, 1993, Waller et al, 2013, Artac et al, 2013), being a woman (Waller et al, 2013, Culica et al, 2002, Thomas et al, 1993), and with socio-demographic factors such as having a job; higher educational level; higher income; and living with a partner (Bender et al, 2012, Boshuizen et al, 2006, Hoebel et al, 2014). Only a few studies have investigated the association of people's morbidity with non-attendance in general health examinations (Dryden et al, 2012, Boshuizen et al, 2006, Thorogood et al, 1993), since it is difficult to obtain records of disease for those who do not want to participate.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Currently, health screening uptake in young men remains low in Malaysia as well as globally. [27][28][29][30][31] The American Time Use Survey found that men aged 25-44 years spent most hours in work-related activities and the least time for personal care, including screening. 32 Compared with women, men are less likely to attend health screening, [33][34][35] which may explain why men have poorer health.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…De maneira geral, os mais pobres são menos propensos a fazer exames de saúde preventivos em relação aqueles com condições socioeconômicas mais favoráveis (HOEBEL et al, 2014). Indivíduos de menor renda buscam por serviços de saúde apenas quando há aparecimento de sintomas das doenças, enquanto aqueles de maior renda procuram os serviços para prevenção e realização de exames rotineiros (MEDEIROS; MENEGHEL, 2012;SOARES et al, 2013).…”
Section: Posição Social E Acesso Aos Serviços De Saúdeunclassified